Mapping the RP2 locus for X-linked retinitis pigmentosa on proximal Xp: a genetically defined 5-cM critical region and exclusion of candidate genes by physical mapping. - Thiselton, D L; Hampson, R M; Nayudu, M; Van Maldergem, L; Wolf, M L; Saha, B K; Bhattacharya, S S; Hardcastle, A J (Genome Research, 1996)
Genetic linkage studies have implicated at least two loci for X-linked retinitis pigmentosa (XLRP) on proximal Xp. We now report a defined genetic localization for the RP2 locus to a 5-cM interval in Xp11.3-11.23. Haplotype analysis of polymorphic markers in recombinant individuals from two XLRP families has enabled us to identify DXS8083 and DXS6616 as the new distal and proximal flanking markers for RP2. Using STS-content and YAC end-clone mapping, an approximately 1.2 Mb YAC contig has been established encompassing the proximal RP2 boundary and extending from T1MP1 to DXS1240 in Xp11.23. Several ESTs have been positioned and ordered on this contig, one of which is novel to the region, identified by sequence data-base match to a physically mapped YAC insert terminal STS. Integration of the genetic and physical data has placed four retinally expressed genes proximal to DXS6616, and thereby excluded them from a causitive role in RP2. This work now provides a much needed focus for positional cloning approaches to isolation of the defective gene.